LA CULTURE DE L’ÉCRIT: LES DÉFIS À L’ÉCOLE ET AU FOYER (Editor: Diane Masny) reviewed by Denise Lussier, followed by THE EROSION OF DEMOCRACY IN EDUCATION: FROM CRITIQUE TO POSSIBILITIES (Editors: J.P. Portelli & R.P. Solomon) reviewed by Ayaz Naseem - Lussier, Denise; Naseem, Ayaz (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2001)
DIANE MASNY (RÉD.). La culture de l’écrit. Les défis à l’école et au foyer. Montréal: Les Éditions LOGIQUES (2001).212 pp. 24.95 (ISBN 2-89381-809-9). J.P. PORTELLI & R.P. SOLOMON (EDS.) The Erosion of Democracy in Education: From critique to possibilities. Calgary: Detselig Enterprises (2001). 328 pp. 26.95 (ISBN 1-55059-214-9).